The relationship between skin symptoms and the scleroderma modification of the health assessment questionnaire, the modified Rodnan skin score, and skin pathology in patients with systemic sclerosis - Ziemek, Jessica (Rheumatology (Oxford), 2016)
Objective. To determine how well skin symptoms considered specific to SSc are captured by patient reported outcomes currently used for assessing patients with SSc, the SHAQ, or skin disease, the Skindex-29; and how well these symptoms correlate with the extent of skin disease on physical exam and skin pathology. Methods. SSc patients completed the scleroderma modification of the Health Assessment Questionnaire (SHAQ), Skindex-29 and a Skin Symptom Assessment questionnaire developed for this study. Correlations were assessed between the Skin Symptom Assessment and SHAQ, Skindex-29, modified Rodnan skin score, and skin pathological features including myofibroblast staining completed on the same date. Results. Tight, hard and rigid/stiff skin symptoms correlated moderately highly with the modified Rodnan skin score (r = 0.445, P = 0.0008; r = 0.486, P = 0.0002; and r = 0.488, P = 0.0002, respectively). Tight skin symptoms correlated moderately with myofibroblast infiltration (r = 0.544, P = 0.0023) and hyalinized collagen (r = 0.442, P = 0.0164), while both hard and rigid/stiff skin correlated moderately with inflammation (r = 0.401, P = 0.0310 and r = 0.513, P = 0.0045), myofibroblast infiltration(r = 0.480, P = 0.0084 and r = 0.527, P = 0.0033) and hyalinized collagen (r = 0.453, P = 0.0137 and r = 0.478, P = 0.0087), while the SHAQ was not found to correlate with any of these pathological changes. In contrast, painful skin symptoms correlated moderately with the SHAQ (r = 0.413, P = 0.0073), and with the three domains of Skindex-29: Symptoms, Emotions and Functioning. Skindex-29 indicates that dcSSc patient skin symptoms are nearly as severe as those of patients with psoriasis or atopic dermatitis. Conclusion. Patient reported skin symptoms correlate with clinical and pathological measures in the skin. A validated patient reported skin symptom instrument might considerably improve evaluation of SSc skin disease.